Modulation of Polyelectrolyte Adsorption on Nanoparticles and Nanochannels by Surface Curvature - Gilles, Facundo Matias (2018)
This paper presents theoretical results on the adsorption of polyelectrolyte chains on surfaces with opposite charge and nanoscale curvature. The theory predicts that increasing the surface curvature can either increase or decrease the amount of adsorbed polyelectrolyte, depending on the type of curvature (convex or concave) and whether the polyelectrolyte undercompensates or overcompensates the initial charge of the substrate. For small bulk salt concentration (10-4 M), increasing the curvature of the surface displaces the adsorption equilibrium of the polyelectrolyte in order to decrease the absolute value of the effective charge density for concave surfaces (nanochannels) or to increase it for convex surfaces (nanoparticles). This behavior is traced back to the dependence of the total free energy as a function of the curvature of the surface. For intermediate salt concentrations (0.01-0.1 M), the magnitude of the effect is larger than that for low salt concentrations, although the general picture becomes more complex due to the fact that the added salt competes with the polycation to screen the negative charge of the substrate. It is argued that the effect under discussion will be relevant for nano-objects that have different radii or type of curvature at different locations (i.e. conical nanochannels or cylindrical nanorods with hemispherical tips) as our theory predicts inhomogeneous polyelectrolyte adsorption on their surfaces.